2015
DOI: 10.1681/asn.2015060634
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Aggravates Cyst Growth in a Model of Polycystic Kidney Disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD), one of the most common monogenetic disorders, is characterized by kidney failure caused by bilateral renal cyst growth. MicroRNAs (miRs) have been implicated in numerous diseases, but the role of these noncoding RNAs in ADPKD pathogenesis is still poorly defined. Here, we investigated the role of miR-21, an oncogenic miR, in kidney cyst growth. We found that transcriptional activation of miR-21 is a common feature of murine PKD. Furthermore, compared with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 57 publications
1
62
0
Order By: Relevance
“…The expression of the miR-17~92 cluster, consisting of miR-17, -18a, 19a, -20a, -19b1 and -92a1, seems to be essential for normal nephrogenesis since ablation of the cluster in a mouse model resulted in reduced numbers of nephrons (Marrone, et al, 2014). Furthermore, miR-21 and miR-150 were found highly enriched in kidney cysts of patients with polycystic kidney disease and kidney biopsies from patients with lupus nephritis, respectively (Lakhia, et al, 2015; H. Zhou, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the miR-17~92 cluster, consisting of miR-17, -18a, 19a, -20a, -19b1 and -92a1, seems to be essential for normal nephrogenesis since ablation of the cluster in a mouse model resulted in reduced numbers of nephrons (Marrone, et al, 2014). Furthermore, miR-21 and miR-150 were found highly enriched in kidney cysts of patients with polycystic kidney disease and kidney biopsies from patients with lupus nephritis, respectively (Lakhia, et al, 2015; H. Zhou, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulation of miR-21 in the kidneys of the PKD/ mhm (cy/+) rat model of ADPKD, compared with that in wild-type controls, has been reported and indicates that miR-21 may be involved in cell proliferation by regulating programmed cell death-4 expression (18). Recent studies have suggested a critical role for miRs in the effort to identify potential therapeutic targets in ADPKD (19)(20)(21). The miR-17-92 miR cluster and miR-21 may promote manifestation of renal cyst growth in PKD mouse models.…”
mentioning
confidence: 99%
“…In Kif3a-KO mice, the miR-17-92 cluster and miR-21 were up-regulated. Cyst growth was reported to be reduced in Kif3a-miR-17-92and Pkd2-miR-21-double-knockout mice compared with Kif3a-and Pkd2-KO mice (19,20). Furthermore, anti-miR-17 treatment attenuated cyst growth in PKD mouse models (21).…”
mentioning
confidence: 99%
“…To further rule out cross reactivity, we analyzed the expression of miR-21, an abundantly expressed, pathogenic miRNA in PKD. 8,11,14,25 miR-21 levels did not change in kidneys from mice treated with PBS compared to kidneys from mice treated with either anti-miR-17, 18, 19, or 25 mixtures ( Fig. 2E).…”
Section: Expression Of Mirnas Produced By the Mir-17~92 And Related Cmentioning
confidence: 90%
“…miRNAs belonging to the one family have redundant biological functions because they target the same mRNAs. In diseases such as cancer [6][7][8][9] , and as we have recently shown in ADPKD 10,11 , aberrant activation of miRNAs can drive disease progression. Accordingly, synthetic oligonucleotides known as anti-miRs have emerged as a novel therapeutic platform to inhibit pathogenic miRNAs.…”
Section: Introductionmentioning
confidence: 94%